Advanced modeling of online consumer behavior: The moderating roles of hedonism and culture - Richard, Marie-Odile; Habibi, Mohammad Reza (Journal of business research, 2016)
This study develops and tests a comprehensive model of online consumer behavior. Using a sample of 1523 subjects from different cultural backgrounds, there is strong support for the model across three different cultures. Since hedonism is one of the important aspects of online shopping, the level of hedonism for 39 websites is measured to investigate how hedonism moderates online consumer behavior and how it interacts with culture. The findings support that consumers' emotions felt after visiting a website positively influence their perceptions of the website atmospherics that in turn influence a set of behavioral variables ending up with intention to purchase. The findings also show that hedonism and culture do interactively moderate online consumers' behavior. Together, this article provides deep new insights in the relative importance of various variables in online consumer behavioral models across cultures and levels of hedonism of websites. Discussions and managerial implications are then presented.